New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia - Bu, Yun; Rezende Souza, Maysa Fernanda Villela; Mayoral, Jaime (Zootaxa, 2021)
Two new species of palpigrades are described: a soil-dwelling species of the genus Koeneniodes Silvestri, 1913 from a broadleaf forest in Tibet and an extraordinary cave-dwelling species from Jinhua cave in China belonging to Prokoenenia Börner, 1901. Koeneniodes tibetanus sp. n. is related to Koeneniodes spiniger from Thailand. The two species share the presence of four thick and spiniform setae on the second lobe of the female genitalia; they differ in the number of thick setae on opisthosomal sternite IV, the number of cheliceral teeth, the coxal setal formula, and the morphology of the spiniform setae. Prokoenenia sarcodactylica sp. n. is based on an immature female from Jinhua Cave, Beijing. The presence of 18 finger-shaped blades in the lateral organs—unique among palpigrades –, the large body size (2150 μm) and the extremely long basitarsus IV (205 μm) indicate that the new species is the first undoubtedly cave–adapted Prokoenenia. This is also the first record of the genus Prokoenenia from China.